2019
DOI: 10.3389/fnagi.2019.00310
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Functional Connectivity Patterns Are Associated With Social and Cognitive Lifestyle Factors: Pathways to Cognitive Reserve

Abstract: The importance of diverse lifestyle factors in sustaining cognition during aging and delaying the onset of decline in Alzheimer’s disease and related dementias cannot be overstated. We explored the influence of cognitive, social, and physical lifestyle factors on resting-state lagged linear connectivity (LLC) in high-density electroencephalography (EEG) in adults, ages 35–75 years. Diverse lifestyle factors build cognitive reserve (CR), protecting cognition in the presence of physical brain decline. Difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 70 publications
5
33
0
Order By: Relevance
“…In essence, the concept of reserve suggests that some initial conditions of brain physiology and function-often measured using neuroimaging techniques-heavily constrain the observed clinical sequelae." Consistent with an increasing number of studies suggesting that RSN organization is associated with reserve level and reflects the influence of reserve on brain network organization (36), in our study, we found that a higher connectivity at baseline could characterize MS patients with a higher functional reserve. Indeed, previous studies have linked altered FC with reduced or preserved functional reserve in MS (37)(38)(39).…”
Section: Functional Reserve Engagement As a Putative Mechanism For Nesupporting
confidence: 91%
“…In essence, the concept of reserve suggests that some initial conditions of brain physiology and function-often measured using neuroimaging techniques-heavily constrain the observed clinical sequelae." Consistent with an increasing number of studies suggesting that RSN organization is associated with reserve level and reflects the influence of reserve on brain network organization (36), in our study, we found that a higher connectivity at baseline could characterize MS patients with a higher functional reserve. Indeed, previous studies have linked altered FC with reduced or preserved functional reserve in MS (37)(38)(39).…”
Section: Functional Reserve Engagement As a Putative Mechanism For Nesupporting
confidence: 91%
“…Taking these data into account, it might be also possible that our results could be modulated by an age-related effect. Nevertheless, in a posterior study, Fleck et al (2019) taking age as a continuous covariate (range age 35-75) and using LLC as well, did not found any significant effect of age, but still important differences in LLC between high and low CR groups. High social CR was related to greater local and long-range LLC in theta and low alpha, and high cognitive CR was associated with greater low alpha long-range LLC between the occipital lobe and other cortical regions.…”
Section: Correlational Analysismentioning
confidence: 77%
“…An inverse correlation between the CSD of delta activity in the occipital region and the CRI was also observed in our study, so the higher the CRI the lower the posterior delta activity. In this line, Sánchez-López et al ( 2018) found less delta and theta activity in participants with high levels of physical activity, considered a protective factor for cognitive function sometimes proposed as another proxy of cognitive reserve (Dik et al, 2003;Fleck et al, 2019). In addition, an increase in delta oscillatory activity has been associated with cognitive dysfunction (Babiloni et al, 2006), and therefore low levels of delta might be considered a neuroprotective factor against cognitive decline.…”
Section: Correlational Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[64][65][66] In the context of typical aging, social isolation and loneliness increase risk of mortality 67 and age-related health problems, such as cardiovascular disease, chronic respiratory diseases, cancer, diabetes, and dementia. [68][69][70] Social isolation is also linked to accelerated brain aging, demonstrated by declines in global cognition 68,[71][72][73][74] and reductions in functional connectivity 75 and peak alpha frequency. 76 However, the link between social isolation and aging outcomes has not been investigated in ASD.…”
Section: Discussionmentioning
confidence: 99%